A Systematic Literature Review on Self-Efficacy, Entrepreneurial Motivation, and Field Experience as Predictors of Entrepreneurial Interest Among Students - Adisty Akhoma Ummah; Rahmiati Rahmiati; Waskito Waskito; Kasmita Kasmita; Murni Astuti (JETL (Journal of Education, Teaching and Learning), 2025)
This systematic literature review addresses the gap in understanding how self-efficacy, entrepreneurial motivation, and field experience influence students' entrepreneurship interest through entrepreneurial attitudes. Despite growing attention to student entrepreneurship, limited comprehensive analysis exists on these key predictors and their integration in educational contexts. Following PRISMA protocol, we systematically searched Scopus database for articles published between 2015-2025. Using predetermined keywords combining self-efficacy, entrepreneurial motivation, field experience, and entrepreneurial intention among students, we identified 482 articles. After rigorous screening applying inclusion and exclusion criteria, 74 articles were selected for comprehensive analysis (15.4% inclusion rate). Data extraction covered bibliographic information, study characteristics, theoretical frameworks, variables, and key findings. Analysis revealed significant temporal growth from 2 articles (2015) to 16 articles (2024), with average 27.92 citations per article and 18.9% high-impact publications (>50 citations). Variable distribution showed entrepreneurial intention dominance (89.2%), followed by entrepreneurial attitude (28.4%) and self-efficacy (23.0%), while entrepreneurial motivation and field experience were critically underexplored (1.4% each). Geographic analysis indicated global context dominance (82.4%) with limited Indonesian research (2.7%). Theoretical framework analysis revealed 91.9% articles lacked explicit theoretical foundation, with Theory of Planned Behavior used in only 5.4% studies. Self-efficacy emerges as the primary psychological predictor supporting Social Cognitive Theory, while entrepreneurial attitude functions as crucial mediator in Theory of Planned Behavior. Critical gaps include absence of integrative models combining all three variables, lack of longitudinal studies (0%), and limited contextual research in Indonesia. These findings provide essential guidance for developing comprehensive entrepreneurship curricula emphasizing self-efficacy development, practical experience integration, and motivation enhancement systems for fostering student entrepreneurship interest.